Population Structure and Genetic Diversity Analysis in Sugarcane (Saccharum spp. hybrids) and Six Related Saccharum Species - Haizheng Xiong; Yilin Chen; San-Ji Gao; Yong-Bao Pan; Ainong Shi (Agronomy, 2022)
Sugarcane (Saccharum spp. hybrids) is one of the most important commercial crops for sugar, ethanol, and other byproducts production; therefore, it is of great significance to carry out genetic research. Assessing the genetic population structure and diversity plays a vital role in managing genetic resources and gene mapping. In this study, we assessed the genetic diversity and population structure among 196 Saccharum accessions, including 34 S. officinarum, 69 S. spontaneum, 17 S. robustum, 25 S. barberi, 13 S. sinense, 2 S. edule, and 36 Saccharum spp. hybrids. A total of 624 polymorphic SSR alleles were amplified by PCR with 22 pairs of fluorescence-labeled highly polymorphic SSR primers and identified on a capillary electrophoresis (CE) detection system including 109 new alleles. Three approaches (model-based clustering, principal component analysis, and phylogenetic analysis) were conducted for population structure and genetic diversity analyses. The results showed that the 196 accessions could be grouped into either three (Q) or eight (q) sub-populations. Phylogenetic analysis indicated that most accessions from each species merged. The species S. barberi and S. sinense formed one group. The species S. robustum, S. barberi, S. spontaneum, S. edule, and sugarcane hybrids merged into the second group. The S. officinarum accessions formed the third group located between the other two groups. Two-way chi-square tests derived a total of 24 species-specific or species-associated SSR alleles, including four alleles each for S. officinarum, S. spontaneum, S. barberi, and S. sinense, five alleles for S. robustum. and three alleles for Saccharum spp. hybrids. These species-specific or species-associated SSR alleles will have a wide application value in sugarcane breeding and species identification. The overall results provide useful information for future genetic study of the Saccharum genus and efficient utilization of sugarcane germplasm resources in sugarcane breeding.